The different pattern of blood S100B protein and GFAP concentrations in ischemic stroke (Faculty of Medicine Universitas Indonesia, 2013)
Background: S100B protein and glial fibrillary acidic protein (GFAP) released during ischemia have been associated with stroke. This study aimed to know whether there was a correlation between the concentration of these markers with the severity of neurological deficit in ischemic stroke. Methods: This was a cross-sectional study, which involved 143 ischemic stroke patients who were admitted to hospital not more than 72 hours after the onset and fulfilled the criteria. The concentration of S100B protein and GFAP was determined by ELISA method. Blood level of S100B and GFAP in patient with mild, moderate, and severe stroke were analyzed with Kruskal-Wallis test. Results: There was a significant difference between S100B protein concentration among subjects with mild (median 63.31 ng/L), moderate (median 88.93 ng/L), and severe (median 511.55 ng/L) NIHSS at admission (p < 0.05). A weak significant correlation was found between the severity of NIHSS and the S100B protein concentration. The more severe the NIHSS, the higher the S100B protein concentration (r = 0.351; p < 0.001). Subjects with moderate and severe NIHSS were more frequent to have an intermediate or high level of S100B protein than the subjects with mild NIHSS (OR = 3.9; p < 0.001). The median concentration of GFAP was significantly higher in severe NIHSS subjects (median 0.374 ng/mL) than its concentration in mild (median 0.047 ng/mL) and moderate (median 0.043 ng/mL) NIHSS subjects (p < 0.05). Conclusion: S100B protein concentration was significantly higher in linier relation with the severity of NIHSS, while the GFAP concentration was significantly higher if the NIHSS had been already severe. (Med J Indones. 2013;22:215-20. doi: 10.13181/mji.v22i4.602) Keywords: GFAP, ischemic stroke, NIHSS, S100B protein